2021
DOI: 10.1017/s1368980020005121
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of health claims regarding creatine monohydrate present in commercial communications for a sample of European sports foods supplements

Abstract: Objective: To analyse the information on health claims present in the labelling of creatine monohydrate (CM) products. Design: A descriptive study of a selection of products marketed as CM, with health claims, and that met the inclusion/exclusion criteria, was conducted using the Amazon and Google Shopping websites. The adequacy and compliance of the health claims were evaluated with the European legislative requirements (European Food Safety Authority and European Commission). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This study identified a high level of variation in the dominant nutrients between each sports food category, such as protein, fat, saturated fat, carbohydrate, and dietary fibre, as has been found by other analytical studies ( 22 , 40 ). This variation may be due to manufacturer determined serving size and recommended serves per day, as well as to the form of the product (e.g., powder, liquid, or bar).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study identified a high level of variation in the dominant nutrients between each sports food category, such as protein, fat, saturated fat, carbohydrate, and dietary fibre, as has been found by other analytical studies ( 22 , 40 ). This variation may be due to manufacturer determined serving size and recommended serves per day, as well as to the form of the product (e.g., powder, liquid, or bar).…”
Section: Discussionsupporting
confidence: 75%
“…The findings also create doubt regarding the accuracy of all nutrition levels provided, the ingredients included and of the veracity of claims displayed on-pack. Analytical studies of claims relating to single ingredients in selected sports foods, concluded similarly that most of the claims made should be either modified or eliminated and could be misleading consumers ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen, product advertising does not always correctly refer to the effects of a particular food. Food fraud can be found in various forms in advertising, consumer information, and marketing of sports supplements, also observed in the study on the analytical assessment of health claims related to caffeine dosage in the labelling of sports supplements [47] and the study on health claims relating to creatine monohydrate [48].…”
Section: Fraud In Advertising and Direct-to-consumer Informationmentioning
confidence: 93%
“…This lack of accurate information also calls into question the accuracy of nutrition content claims and general-level health claims, both of which are dependent on the stated nutrient information [ 12 , 17 , 18 ] and are important in consumer food-choice decisions [ 19 , 20 , 21 , 22 ]. Non-athletes, who may not have the benefits of dietetic guidance like athletes, could be consuming multiple sports food products using inaccurate packaging information and relying on nutrition claims that do not truly reflect the food item being considered [ 23 , 24 ], leading to overconsumption risks, potential side effects, and overall poor health outcomes. Therefore, it is important to examine the contemporary situation of the factors influencing consumption, including the role of packaging information, risk perception, and experiences of side effects.…”
Section: Introductionmentioning
confidence: 99%